2018
DOI: 10.1136/bjophthalmol-2018-311963
|View full text |Cite
|
Sign up to set email alerts
|

Five-year visual outcomes after anti-VEGF therapy with or without photodynamic therapy for polypoidal choroidal vasculopathy

Abstract: A PRN regimen for PCV may have a limited effect for the long-term maintenance of improved VA. Macular atrophy may occur more frequently with combination therapy and is possibly associated with the 5-year VA. Thus, combination therapy should be carefully selected for patients susceptible to macular atrophy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 24 publications
(25 reference statements)
1
18
1
Order By: Relevance
“…Several studies reported long-term results of the combination therapy involving PDT and anti-VEGF agents for PCV. [13,16,17] Miyata et al reported 5-year results after combination therapy involving PDT and intravitreal injection of ranibizumab for 20 eyes with PCV. In their report, BCVA significantly improved at 1 year, but thereafter BCVA declined and returned to baseline value at 5 year.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies reported long-term results of the combination therapy involving PDT and anti-VEGF agents for PCV. [13,16,17] Miyata et al reported 5-year results after combination therapy involving PDT and intravitreal injection of ranibizumab for 20 eyes with PCV. In their report, BCVA significantly improved at 1 year, but thereafter BCVA declined and returned to baseline value at 5 year.…”
Section: Discussionmentioning
confidence: 99%
“…[7] Since the follow-up period was short in most studies reporting the combination therapy, [8][9][10][11][12] there has been few reports investigating 5-year outcome of combination therapy of PDT and intravitreal injection of anti-VEGF agent for PCV. [13] In the present study, we report 5-year visual and anatomical outcomes after combination therapy of PDT and intravitreal injection of ranibizumab or aflibercept for PCV and the predictive factors for visual outcomes at 5 years and time to recurrence during the follow-up.…”
Section: Introductionmentioning
confidence: 93%
“…Miyata et al reported that BCVA improved relative to the baseline only in the first year and not after 3 to 5 years. Moreover, CRT after 5 years was reported to be similar to the baseline CRT 30 . Wataru et al detected a similar deterioration of BCVA improvement after 3 years.…”
Section: Discussionmentioning
confidence: 74%
“…However, several reports have indicated that repeated PDT might damage the retinal pigment epithelium and choriocapillaris layer 32 , 33 . In addition, Miyata et al reported a marginally significant increase ( P = 0.06) in rate of macular atrophy in the combination therapy group, and they considered repeated PDT to be related to macular atrophy in the long term 30 . Nonetheless, there is still no sufficient evidence regarding the long-term consequences of PDT.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Miyata et al reported the five-year results of therapy combining anti-VEGF drugs with PDT for PCV. The combination therapy with PDT was more likely to result in macular atrophy than that with anti-VEGF alone [ 20 ]. Son et al compared half-dose versus full-dose PDT for CSC and found no difference in macular atrophy at three years between the two groups [ 21 ].…”
Section: Discussionmentioning
confidence: 99%